(untitled) (The Review of Diabetic Studies, 2024)
Background: Improving patient safety and healthcare disparities in nursing practice requires that culturally responsive teaching is incorporated into practice. Yet integration in nursing education is hindered by faculty resistance, lack of resources and inconsistent implementation. Aim: The objective of the present systematic review is to review culturally responsive teaching strategies in nursing education and their effect on nursing practice and patient safety. Method: The studies selected were synthesized, all of which were published between 2020 and 2024 in all major databases. The focus was on cultural competence in nursing education, barriers to integration, faculty development, and patient safety outcomes of ten selected studies. Results: A review discovered that culturally responsive teaching methods, such as case-based learning and simulation exercises, greatly increase nursing students’ cultural competence and patient communication skills, resulting in improved patient care. Barriers existing can be faculty resistance, lack of resources, and lack of institutional support, however. It is noted that nurses with cultural competence training offer to result in improved patient safety, less clinical errors, and improved patient provider relationships. A critical factor for the successful integration of cultural competence into nursing curricula was highlighted as the ongoing faculty development. Conclusion:Culturally responsive education has an important role to play in improving patient safety and closing healthcare disparities. To gain universal integration, nursing schools need to eliminate obstacles by having faculty training and by having sufficient resources. Effective culturally responsive practice will improve patient outcomes and quality of care.